Reproduction in mammals the female perspective - Hayssen, Virginia Douglass (Johns Hopkins University Press, 2017)
"Humans typically have only one baby at a time following nine months of pregnancy, but other mammals have 20 or more young after only a few weeks in utero. What causes this incredible reproductive diversity? Reproduction in Mammals is a fascinating examination of the diverse reproductive strategies of a broad spectrum of mammals and the ways in which natural selection has influenced that diversity. While accounts of reproduction in individual taxa abound, this unique book's comprehensive coverage gathers stories from many taxa into a single, cohesive perspective that centers on the reproductive lives of females. The authors shed light on intriguing questions such as: Do bigger moms have bigger babies? Do primates have longer pregnancies than other groups? Do aquatic animals have particular patterns? Do carnivores like lions often produce larger litters than prey species? The book opens with the authors' definition of what constitutes a female perspective and an examination of the evolution of reproduction in mammals. It then outlines the individual female: her genetics, anatomy, and physiology. From this nuanced basis, the text progresses to mirror the female reproductive cycle and includes her interactions with males and offspring. The final section contextualizes the reproductive cycle within the rest of the world - both abiotic and biotic environments. To close, the authors include dedicated chapters on human concerns: conservation and women as mammals. Readers will come away from this thought-provoking book with an understanding not only of how reproduction fits into the lives of female mammals but also of how biology has affected the enormously diverse reproductive patterns of the phenotypes we observe today."--